1991
DOI: 10.1295/polymj.23.925
|View full text |Cite
|
Sign up to set email alerts
|

Stiff-Chain Nature of Poly(1-phenyl-1-propyne) in Dilute Solution

Abstract: ABSTRACT:Light scattering and viscosity measurements were made on twelve narrowmolecular weight distribution samples ofpoly(l-phenyl-1-propyne) in toluene and in cyclohexane. In cyclohexane at 36°C, the second virial coefficient A2 vanished, the mean-square radius of gyration increased linearly with weight-average molecular weight Mw, but the intrinsic viscosity was not proportional to M!1 2 • Thus poly(l-phenyl-1-propyne) in cyclohexane at 36oC is an unperturbed semiflexible polymer. A2 in toluene was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…From the intercepts and slopes of the lines, we have determined the weight-average molecular weight M w and the second virial coefficient A 2 for those fractions. Values of A 2 of PCPA in DMSO are comparable to those of a polyacetylene derivative with a similar chemical structure, poly(1-phenyl-1-propyne) (PPP), in toluene (a good solvent) studied by Hirao et al, 13 indicating that DMSO is a good solvent for PCPA.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…From the intercepts and slopes of the lines, we have determined the weight-average molecular weight M w and the second virial coefficient A 2 for those fractions. Values of A 2 of PCPA in DMSO are comparable to those of a polyacetylene derivative with a similar chemical structure, poly(1-phenyl-1-propyne) (PPP), in toluene (a good solvent) studied by Hirao et al, 13 indicating that DMSO is a good solvent for PCPA.…”
Section: Resultssupporting
confidence: 51%
“…In the previous study, Hirao et al 13 analyzed [η] and also the radius of gyration 〈S 2 〉 1/2 data for PPP in toluene and cyclohexane using the wormlike chain (cylinder) model to estimate the molar mass M L per unit contour length and the persistence length q. They found that to fit both [η] and 〈S 2 〉 1/2 data with the same M L and q, the Flory-Fox constant Φ ∞ must be smaller than the theoretical one ()2.87 × 10 23 ).…”
Section: Resultsmentioning
confidence: 90%
“…This was also confirmed in a recent investigation on poly(1-phenyl-1-propene) in toluene by Hirao et al, 179 where second virial coefficients were determined by light scattering and by sedimentation equilibrium over a wide range of molar mass. Since the measurement of thermodynamic data by sedimentation equilibrium is not very frequent in the literature this is certainly not a final statement.…”
Section: Ultracentrifugesupporting
confidence: 73%
“…Plots of log-\ 2 <S 2 ) vs. log,\£ constructed from reported <S 2 ) data for PHIC in hexane (0), 6 CTDC in NMP (e), 13 • 14 Na-HA in 0.5M aqueous NaCl (0), 17 and PPP in toluene (6). 18 Solid line, eq 1; dashed line, empirical fit to the Na-HA data.…”
Section: Model Parameters and Onset Of Volume Effectmentioning
confidence: 99%